Gold nanoparticle-based optical nanosensors for food and health safety monitoring: recent advances and future perspectives - Nguyen, Ha Anh (Royal Society of Chemistry, 2022)
Modern society has been facing serious health-related problems including food safety, diseases and illness. Hence, it is urgent to develop analysis methods for the detection and control of food contaminants, disease biomarkers and pathogens. As the traditional instrumental methods have several disadvantages, including being time consuming, and having high cost and laborious procedures, optical nanosensors have emerged as promising alternative or complementary approaches to those traditional ones. With the advantages of simple preparation, high surface-to-volume ratio, excellent biocompatibility, and especially, unique optical properties, gold nanoparticles (AuNPs) have been demonstrated as excellent transducers for optical sensing systems.